2007
DOI: 10.1073/pnas.0708222104
|View full text |Cite
|
Sign up to set email alerts
|

α-Helices direct excitation energy flow in the Fenna–Matthews–Olson protein

Abstract: In photosynthesis, light is captured by antenna proteins. These proteins transfer the excitation energy with almost 100% quantum efficiency to the reaction centers, where charge separation takes place. The time scale and pathways of this transfer are controlled by the protein scaffold, which holds the pigments at optimal geometry and tunes their excitation energies (site energies). The detailed understanding of the tuning of site energies by the protein has been an unsolved problem since the first high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(121 citation statements)
references
References 37 publications
6
115
0
Order By: Relevance
“…Site energies were derived from structure-based calculations of the free energy change of the protein-pigment complex (PPC) that occurs when the ground state charge density of Trp m is shifted to the first excited state, analogous to methods used for the FMO complex [26,61,62]. Quantum chemical calculations of the pigments in vacuo yield the charge distributions of the S 0 and 1L a states and a contribution DE qm to the S 0 !…”
Section: Vertical Excitation Energies For Tryptophan/site Energy Calcmentioning
confidence: 99%
See 1 more Smart Citation
“…Site energies were derived from structure-based calculations of the free energy change of the protein-pigment complex (PPC) that occurs when the ground state charge density of Trp m is shifted to the first excited state, analogous to methods used for the FMO complex [26,61,62]. Quantum chemical calculations of the pigments in vacuo yield the charge distributions of the S 0 and 1L a states and a contribution DE qm to the S 0 !…”
Section: Vertical Excitation Energies For Tryptophan/site Energy Calcmentioning
confidence: 99%
“…As persistent electronic coherences may be a general property of any system of compact nearly static chromophores coupled to the environment [24], we investigate the biological feasibility of coherent energy transfer in the tubulin dimer. Via a combination of homology modelling, molecular dynamics (MD) simulations, quantum chemistry and optical biophysics, we apply structure-based simulations similar to current studies of the FMO complex [25,26], and larger LHCs [27] to probe potential energy transfer mechanisms in tubulin, and by extension microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…The FMO pigment-protein complex from Chlorobium tepidum serves as a model system for photosynthetic energy transfer processes (2,(10)(11)(12)(13). This complex conducts energy from the larger light-harvesting chlorosome to the reaction center in green sulfur bacteria (14,15).…”
mentioning
confidence: 99%
“…As a result, numerous studies of the site-energy distributions and exciton dynamics have been reported [222], and have included explicit investigations of the influence of variations in BChl conformation [64,65,104,225]. So far, the best agreement between structure-based ab initio calculations of the site-energies with those empirically determined by parametric fitting to the experimental spectra, have been obtained by consideration of the effect of the electrostatic environments of the BChl binding-sites on the relative stabilities of their ground-and excited-states [226,227].…”
Section: Fmo Proteinmentioning
confidence: 99%